Mechanistic understanding and the rational design of a SiO2@CD catalyst for selective protection of l-lysine. Issue 3 (20th December 2022) - Li, Pinyi; Fu, Xue; Zhou, Qiang; Fu, Xuewen; Wang, An; Zhang, Guolin; Jiao, Wei; Wang, Chun
Abstract : The mechanism of the selective protection of l -lysine mediated by β-cyclodextrin (β-CD) was investigated by preliminary experiments. The existence of (1a·CD )′ and 1a·CD·2a was proved to be critical for the selectivity and catalytic efficiency. Abstract : The mechanism of the selective protection of l -lysine mediated by β-cyclodextrin (β-CD) was investigated by preliminary experiments, including the reaction efficiency influenced by different reaction conditions, and the existence of (1a·CD )′ and 1a·CD·2a was evidenced by ESI-MS and 2D Rotating Frame Overhauser Effect Spectroscopy (ROESY) analysis. The results indicated that the formation of (1a·CD )′ is critical for the product selectivity and the further formation of the ternary complex 1·CD·2 is responsible for the reaction efficiency. Thus, the yields and selectivity were significantly influenced by the structure, size and reactivity of the reactants. During the mechanistic investigations, we realized that the formation of the product and the β-CD complex at the final stage of the reaction would cause difficulty in product purification by a previously reported homogeneous method. In light of this understanding, an efficient and practical protocol for selective protection of l -lys based on a heterogeneous catalyst SiO2 @CD was developed. The use of the SiO2 immobilized β-CD catalyst prevented the formation of the "capped" products by controlling the spatial rearrangement of β-CDs on solid supports, which represents a considerable synthetic improvement over the tedious and wasteful organic solvent extraction for product purification.